Penerapan Model Pembelajaran Kooperatif Tipe Think-Pair-Share (TPS) Dalam Meningkatkan Hasil Belajar Peserta Didik Pada Mata Pelajaran Pendidikan Pancasila Kelas IV Madrasah Ibtidaiyah Negeri 2 Tanjung Jabung Timur Jambi - Winaryo; Dian Citra Lestari; Yudo Handoko (BULLET : Jurnal Multidisiplin Ilmu, 2023)
The Think-Pair-Share (TPS) cooperative learning model is a cooperative learning that gives students time to think and respond. The purpose of this is to determine the success of applying the Think Pair Share learning model in improving student learning outcomes in class IV Pancasila education subjects at Tanjung Jabung Timur Jambi 2 Elementary School. action research). This research is planned to take place in 2 cycles so that there is an increase in learning outcomes through the learning strategy of applying the Think-Pair-Share (TPS) Cooperative Learning Model. Regarding the stages in classroom action research, there are several experts who put forward a classroom action research model with different sections. -different, but in general there are four stages, namely: (1) planning (2) implementation (3) observation (4) reflection. The results showed that the activities of students during the learning process of the History of the Basic Formulation of the Indonesian State and attitudes and behavior according to Pancasila values by using the Cooperative learning model of the Think-Pair-Share Type ((TPS), in cycle I, good category (2.80 ), in cycle II it increased to (3.85) with a very good category.Student learning outcomes that applied the History of the Basic Formulation of the Indonesian State and attitudes and behavior according to Pancasila values by using the Think-Pair-Share Type Cooperative learning model ((TPS), in cycle I the number of students who achieved learning mastery was 15 students with a percentage of 83.33%, while in cycle II the number of students who achieved learning mastery was 18 students with a percentage of 100%.